KEPRIBADIAN PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Samsul Riza; Hemawati (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2020)
Personality is a term that is no stranger to being heard especially in the discipline of the world of education. Because in its own purpose education is seen as an effort in forming a better personality. The familiarity of the term